PRELIMINARY STUDY ON PROPERTIES OF ISOLATED CELLULOSE FIBERS FROM OIL PALM FRONDS BY CHEMO-MECHANICAL PROCESS - Noor Afeefah, Nordin; Othman, Sulaiman; Rokiah, Hashim; Mohamad Haafiz, Mohamad Kassim; Mohamed Nasir, Khan; Junidah, Lamaming (2015)
This study aimed to investigate the properties of isolated cellulose fibers from oil palm frond (OPF) biomass using both chemical and mechanical treatments. The multi-step process of obtaining the cellulose fibers in this work began with the removal of waxes, pectin and other extractives from the OPF by soxhlet extraction process using ethanol and toluene. It was then followed by bleaching process using sodium chlorite and acetic acid. The bleached fibers were subsequently washed with distilled water until pH 7 was obtained before they were being subjected to acid hydrolysis using sulphuric acid. The cellulose fibers were characterized using x-ray diffractions (XRD), transmissions electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). The results showed that the crystallinity index of the extracted cellulose fibers was 45.76 %. From the TEM analysis, the average dimensions of the fibers were 10.57 nm in diameter and 524.65 nm in length. The results from FTIR analysis showed some peaks were shifted due to removal of some components in the fibers. These isolated fibers can be used in many applications such as in medical field, food industry, cosmetics, wood products and etc.